Christianity. - Brown, Alan. (Laguna Hills, CA QEB Publishing, Inc., 2006)
Explore the fascinating world of Christianity and discover how the son of a carpenter started one of the most popular religions in the world. Explore its art, find out about its famous followers, and learn about Christian beliefs, traditions, and colorful festivals.
5 - 9
Keywords: Religions; World of Faiths